Why Can't This Patient Look Up? Bilateral Vertical Gaze Palsy. Issue 12 (23rd April 2015) - Surapaneni, Krishna; Ferguson, Lisa; Altschuler, Eric L.
Abstract: We report a case of a patient with profound bilateral vertical gaze palsy resulting from a unilateral thalamic lesion—one of only a handful of such cases ever reported. The patient had significant symptomatic vertical diplopia that was disabling functionally and vocationally. We discuss pathways whereby a unilateral lesion can cause bilateral gaze palsy. We also report on the successful functional and vocational rehabilitation of the patient's vertical diplopia. To our knowledge, this is the first report of successful rehabilitation of a patient with bilateral vertical diplopia due to a central lesion.